Educational Computer Game for Eartquake - Ebru YILMAZ İNCE; Murat Emre SANCAK (Journal of Learning and Teaching in Digital Age, 2022)
Earthquakes are the movements of the earth's crust that originate in the ground, and they are one of the natural disasters that frighten people because they occur suddenly and often cause great loss of life and property. Earthquake natural disaster is the reality of Turkey and it is important to raise public awareness on this issue. Thanks to the sound effects, realistic animations and three-dimensional virtual environments used in the development of computer games developed in today's technologies, they attract more attention from the players. Digital computer games are used for educational purposes in various fields, enabling learners to increase their motivation towards the relevant subject. It is important to develop educational digital games using up-to-date technologies and present them to young people in accordance with learning. In this study, an educational three-dimensional computer game describing what to do before, during and after the earthquake was developed using the Unity game engine and C# coding language. It is thought that the features of the earthquake educational computer game will attract the attention of everyone from seven to seventy with its three-dimensional virtual environment and educational content, and it can be used for educational purposes in order to increase their motivation for gaining knowledge and experience about earthquakes.